Nutrient stability and sorption of sewage sludge biochar prepared from co-pyrolysis of sewage sludge and stalks / mineral materials. Issue 1 (1st January 2020) - Duan, Xing-Yu; Cao, Yang; Liu, Tao-Ze; Li, Ling; Wang, Bing; Wang, Xiao-Dan
ABSTRACT: The pyrolysis treatment can effectively reduce the sewage sludge volume and fix its nutrients for land application. The synergistic effect on the fixation of nutrients can be better exerted by the sewage sludge biochars (SSB) prepared by the co-pyrolysis method. In this study, SSB was prepared by adding stalks and mineral materials in to sewage sludge that was used as the base material. The element composition, nutrient stability, and adsorption effect of SSB, as well as the feasibility of applying modified SSB in reducing soil nutrients leaching, were discussed in this study. The results indicate that the modified SSB reduced the amount of nitrate leaching and has the ability to remove nutrients in the solution, among which the removal effect of nitrate is better. Moreover, the modified SSB is added to the soil by leaching experiments in soil columns, which can reduce the leaching of nutrients.